2008
DOI: 10.17221/1979-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Nitrofuran antibiotics: a review on the application, prohibition and residual analysis

Abstract: Nitrofuran antibiotics, employed for the treatment of bacterial diseases in livestock production, were banned from use in the European Union (EU) in 1995 due to concerns about the carcinogenicity of their residues in edible tissue. This review provides an overview of nitrofuran toxicity, metabolism, and also specific aspects of legislation surrounding their prohibition. Special attention is devoted to semicarbazide -a nitrofuran metabolite and food contaminant. Analytical procedures for nitrofuran analysis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
130
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(141 citation statements)
references
References 83 publications
(98 reference statements)
0
130
1
6
Order By: Relevance
“…However, since the early 1990s, various experimental animal studies have shown that nitrofurans and their metabolites have potential mutagenicity and genotoxicity [2]. As a consequence, nitrofurans have been banned for use in animal husbandry in the European Union (EU) and other countries [2]. The EU has set the minimum required performance limits (MRPLs) to be 1 μg kg -1 for each nitrofuran metabolite in food of animal origin [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, since the early 1990s, various experimental animal studies have shown that nitrofurans and their metabolites have potential mutagenicity and genotoxicity [2]. As a consequence, nitrofurans have been banned for use in animal husbandry in the European Union (EU) and other countries [2]. The EU has set the minimum required performance limits (MRPLs) to be 1 μg kg -1 for each nitrofuran metabolite in food of animal origin [3].…”
Section: Introductionmentioning
confidence: 99%
“…Instrumental analytical methods such as liquid chromatography with ultraviolet (UV) or UV photodiode array detection and the coupling of high performance liquid chromatography and liquid chromatography electro-spray ionisation to tandem mass spectrometry (HPLC-MS/MS and LC-ESI MS/MS, respectively) are well established for the determination of nitrofuran antibiotics and their metabolites. A detailed review on the residual analysis of nitrofurans and their metabolites was recently published by Vass et al [2]. The instrumental methods can offer high sensitivity and specificity and have the potential for simultaneous determination of several nitrofurans, but the associated highcosts, time-consuming labour requirements and practicalities of the instrumentation have inhibited broadening the scope of monitoring particularly to field-screening scenarios.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its potential carcinogenicity, genotoxicity and mutagenicity to human health, the European Union and U.S. Food and Drug Administration have banned the utility of NFZ in foodproducing animals. However, in some developing countries including China, it is still widely used in the livestock and fishery aquaculture owing to its low production cost, easy availability and high efficiency (Hong et al, 2015;Kwon, 2017;Vass et al, 2008). As a result, NFZ residues and its toxic biological metabolite semicarbazide are often detected in diverse aquatic species and products as well as aquaculture pond water and sediments (Vass et al, 2008;Yu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, in some developing countries including China, it is still widely used in the livestock and fishery aquaculture owing to its low production cost, easy availability and high efficiency (Hong et al, 2015;Kwon, 2017;Vass et al, 2008). As a result, NFZ residues and its toxic biological metabolite semicarbazide are often detected in diverse aquatic species and products as well as aquaculture pond water and sediments (Vass et al, 2008;Yu et al, 2013). In order to eliminate the ecological impact of NFZ on water environment, the efficient degradation of NFZ and elimination of its antibacterial activity are very important during livestock wastewater treatment and aquaculture pond water remediation.…”
Section: Introductionmentioning
confidence: 99%